Evaluation of the Antifungal Efficacy of Acacia Niloticia, Ocimum Tenuiflorum incorporated into Short Term Soft Denture Liner: An In Vitro Study - Shilpa S; Shruthi C S; Poojya R; Pooja Magadum; Akhil K Bilagi (RGUHS Journal of Dental Sciences)
Background and Objectives Soft liner materials though widely used in prosthodontics have some physical and microbiological disadvantages. One such problem is the colonization of the denture surface by Candida albicans thereby causing denture stomatitis. This study aims to evaluate and compare the inhibitory efficacy of Acacia Ocimum and Nystatin.Methodology A total of 75 specimens were prepared by adding Ocimum Acacia or Nystatin to a commercially available soft liner in increasing order of concentrations. 5 ml of Sabouraud Dextrose broth SDB was poured into each test tube and autoclaved. The broth was inoculated with an entire loop of C. albicans for 24 hours at 37ordmC. Discs were placed in the test tube and incubated for 24 hours at room temperature. The broth was removed with a sterile pipette after incubation. Discs were rinsed with sterile water to remove unattached C. albicans and sonicated in sterile water to remove surface organisms. The attached C. albicans were measured by inoculating on Sabouraud Dextrose agar SDA.Results Nystatin showed higher antifungal activity against C. albicans compared to Acacia nilotica and Ocimum tenuiflorum and it was statistically significant. A. nilotica showed better antifungal activity than O. tenuiflorum which was statistically significant. The higher concentration of these agents exhibited better antifungal activity and the difference was statistically significant.Conclusion Nystatin showed the best inhibitory effect on C. albicans followed by A.nilotica and O. tenuiflorum. The Inhibitory effect increased statistically on increasing the concentration of these additives.